Equity Research : Mota Engil SGPS - Moreira, Pedro Miguel Rodrigues Valério Da Silva (2013)
Equity Valuation has been since the beginning a generator of controversy among authors. New methods have been developed throughout time and even though they are clearly justified, weakenesses have been pointed to each one. The growth, increased speed and connection of modern economies, implies a more detailed and appropriate valuation of corporations. The purpose of this dissertation is to provide a general view over the concept and methods of equity valuation, through a review of the extensive literature and the valuation of Mota-Engil SGPS.